SOMALI PAREMIAS AND THEIR RUSSIAN EQUIVALENTS - Kapchits, Georgi (Proverbium - Yearbook, 2020)
It has long been noticed that paremias (proverbs, sayings etc., with all the differences of languages and cultures of the peoples who created them, are alike. This is due to the nature of paremias. As Russian folk-lorist G. L. Permyakov established, “they are signs and models of certain situations or certain relations between objects.” And since the situations that people encounter are the same everywhere, the paremias, invented by them to describe these situations, coincide in meaning. This fully applies to Somali and Russian proverbs and sayings. Some of them coincide al-most textually, some others differ in the images used in them. Proverbial sentences can be closed (proverbial class) and open (proverbial phrases class). At the same time, depending on the type of the motivation of their general meaning (transferred, direct or not immediate), they are divided into six subclasses: proverbs proper, folk aphorisms, non-divided sentences, proverbial phrases proper, by-words and non-divided phrases. In addition, proverbial sentences can be simple and complex (syn-tactically), they have different “goals of utterance” (that is, they can be affirmative or negative), they have a modality (they can be narrative, hortatory and interrogative). Thus, the Somali and Russian paremias, which coincide in meaning, may differ not only in the images used in them, but also in their linguistic and paremiological structures. Of the three main structures of all proverbs and sayings – linguistic (and compositional) structure, logical (and semiotic) structure and object-im-age structure, the coincidence in their logical structure and in the types of things opposed in them, i.e, the coincidence in their meaning, is cru-cial for determining their similarity.